Peculiarities of remote-piloted vehicles on-board navigation complex construction - Mykyichuk, Mykola; Markiv, Volodymyr (Lviv Polytechnic National University, 2018)
The article dwells upon the peculiarities of on-board navigation complex construction. It is highlighted that the optimal method for constructing on-board navigation complex is integration into single complex of sensors and systems with the integration of measurement information. The core of on-board navigation complex should be built on the basis of free-form inertial navigation system. To ensure the piloting tasks, the on-board equipment includes system of air signals. On the basis of the air signals system and magnetic compass air course counting is performed, which together with the inertial calculation allow to obtain comprehensive solution in an autonomous mode. It is important to include in the on-board navigation complex receiver of GNSS signals. Thus, the ideology of constructing the on-board navigation complex initially consists in the integration of measurements from the sensors and systems that make up its structure. It is emphasized that directly on-board navigation complex consists from inertial sensors, GNSS and magnetic compass receivers and also interface with air signal system. Specific types of sensors and systems are selected in accordance with the requirements of software and algorithmic support of onboard navigation complex.
Keywords: Remote-piloted vehicle; On-board navigation complex; Navigation system; System sensors